A psicologia da educação na formação do professor: contribuição na construção de saberes docentes a partir dos olhares de estagiários da Universidade de Caxias do Sul - Canuto, Zita (Universidade do Vale do Rio do Sinos, 2007)
Teacher Formation outstands as one of the most investigated themes in many research papers carried out in the area of Education in the last decades. Many studies have tried, through several and different paths, to study the formation of a teacher, the nature and constitution of the teaching work and its multiple faces. The current study aimed at the identification of the teaching knowledge built during the undergraduate course for Teacher’s Education, starting from what was learned on the classes for Education Psychology. The study was developed with the intent of giving the students taking Teacher’s Education the chance to talk about their own academic formation. Data for this study were obtain by means of semi-structured interviews with eight undergraduate students from different majors. All students that were interviewed were studying for the last semesters of their courses, and were having supervised professional training practices with groups of students in education institutions belonging to the private
Keywords: formação de professores; Universidade de Caxias do Sul; aprendizagem significativa; psicologia da educação; saberes docentes; significant learning; teachers’ formation; teaching knowledge; education psychology; Ciências Humanas